The Localisation of a Global Management Control System - Cruz, I.; Scapens, R.; Major, M. (Accounting, Organizations and Society, 2011)
This study examines how the management control system designed at the head office of an increasingly globalised hotel chain was enacted within one of its sub-units; a joint venture operating in the hospitality industry in Portugal. We found that the practices which comprised the global management control system were reproduced within this joint venture. Yet, at the same time, its managers made the global system 'work' for them, thereby producing variety. Albeit our findings are in line with Barrett, Cooper, and Jamal's (2005) study, which was inspired by Giddens (1990, 1991), we interpret them somewhat differently as we draw on the work of Robertson (1992, 1995). We view localisation as a process through which heterogeneous practices can emerge to facilitate the homogenising tendencies of globalisation by complementing, rather than undermining or opposing, it. As a result, the local can differentiate itself from the global. Also, by linking our findings to the notion of situated functionality in Ahrens and Chapman (2007), we argue that this heterogeneity can be produced when organisational members, whatever their level in the organisation, seek to achieve both the corporate and their own specific objectives